KEEFEKTIFAN MEDIA PEMBELAJARAN “NILA” TERHADAP HASIL BELAJAR SISWA KELAS II PADA MATERI NILAI-NILAI PANCASILA - Belinda Revi Junian; Ilmawati Fahmi Imron; Endang Sri Mujiwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pancasila Education learning in grade 2 of Jegreg Elementary School still uses teacher's books and student's books, making students less active and having difficulty understanding the material on Pancasila values. Based on the results of observations and interviews, out of 25 students only 8 achieved the KKTP score (75). This study aims to determine the effectiveness of using interactive multimedia